2013
DOI: 10.1038/labinvest.2012.164
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic indicators for specimen degradation

Abstract: Variable degrees of molecular degradation occur in human surgical specimens before clinical examination and severely affect analytical results. We therefore initiated an investigation to identify protein markers for tissue degradation assessment. We exposed 4 cell lines and 64 surgical/autopsy specimens to defined periods of time at room temperature before procurement (experimental cold ischemic time (CIT)-dependent tissue degradation model). Using two-dimensional fluorescence difference gel electrophoresis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 66 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…Another potential QC marker for cold ischemia is based on Western Blot analysis of the ratio of intact α-II spectrin and its breakdown products. 23 However, it is not easy to standardize a Western Blot assay, particularly in FFPE tissue where extracting intact proteins of large molecular mass is difficult (intact α-II spectrin is 250 kDa).…”
Section: Discussionmentioning
confidence: 99%
“…Another potential QC marker for cold ischemia is based on Western Blot analysis of the ratio of intact α-II spectrin and its breakdown products. 23 However, it is not easy to standardize a Western Blot assay, particularly in FFPE tissue where extracting intact proteins of large molecular mass is difficult (intact α-II spectrin is 250 kDa).…”
Section: Discussionmentioning
confidence: 99%
“…A ‘quality measure’ in one context may not be relevant for a different assay or application 22,23 . There have been attempts to measure intrinsic quality indicators, but these can be technically complex and have not been adopted routinely 24 . There is currently no universally accepted method for screening tissue sample quality before use, ideally one that is cheap, rapid, technically simple and relatively non‐destructive or invasive.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 There have been attempts to measure intrinsic quality indicators, but these can be technically complex and have not been adopted routinely. 24 There is currently no universally accepted method for screening tissue sample quality before use, ideally one that is cheap, rapid, technically simple and relatively nondestructive or invasive. Some tissues are not properly annotated, and therefore the design and interpretation of assays can be difficult.…”
mentioning
confidence: 99%
“…These studies identified a small number of proteins that changed in abundance (primarily as a result of degradation, presumably via proteolysis) after long (Ͼ 3 h) periods of cold ischemia (19,20). For example, Li et al, using two-dimensional fluorescence difference gel electrophoresis in conjunction with mass spectrometry, identified 26 proteins that changed over 48 h of cold ischemia time, chiefly as a result of degradation (20). The sample collection and analysis approaches used in most of these studies did not permit assessment of changes within the one-hour interval investigated in our study.…”
mentioning
confidence: 99%